2007
DOI: 10.1136/bjo.2006.112060
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of vancomycin following intracameral bolus injection in patients undergoing phacoemulsification cataract surgery

Abstract: Following bolus intracameral injection at the end of cataract surgery the concentration of vancomycin in the anterior chamber vastly exceeds its MIC for at least 24 hours but is predicted to fall below the MIC after 33 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…Montan et al [15] reported that the median intracameral level of cefuroxime was 2742 mg/l at 30 s and 756 mg/l at 60 min after drug instillation. They also reported that the actual half-life of cefuroxime may be closer to 1-2 h, and cefuroxime levels in the aqueous humor exceeding minimal inhibitory concentrations for several relevant species will persist for 4 to 5 h. On the other hand, the half-life of vancomycin in the anterior chamber was estimated to be approximately 3 h 16 min [1]. Furthermore, Ferro et al [21] found a 47% decrease in aqueous vancomycin concentration within 2 h after surgery using vancomycin 20 mg/l in the infusion.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Montan et al [15] reported that the median intracameral level of cefuroxime was 2742 mg/l at 30 s and 756 mg/l at 60 min after drug instillation. They also reported that the actual half-life of cefuroxime may be closer to 1-2 h, and cefuroxime levels in the aqueous humor exceeding minimal inhibitory concentrations for several relevant species will persist for 4 to 5 h. On the other hand, the half-life of vancomycin in the anterior chamber was estimated to be approximately 3 h 16 min [1]. Furthermore, Ferro et al [21] found a 47% decrease in aqueous vancomycin concentration within 2 h after surgery using vancomycin 20 mg/l in the infusion.…”
Section: Discussionmentioning
confidence: 94%
“…Murphy et al [1] used 1 mg/0.1 ml vancomycin via bolus intracameral injection in their study, and reported that it is possible that lower and potentially safer doses could be as effective in preventing endophthalmitis. Because of the definite risk of dosage errors, they also recommended that vancomycin should be prepared for bolus intracameral injection in the hospital pharmacy and not in the operating theatre.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The chitosan was characterized by determining its viscosity-average molecular weight, M v , by dilute-solution viscometry using a Schott-Gerate AVS 300 Automatic Viscosity Measuring System. The solvent used was an aqueous solution containing 0.2M acetic acid, 0.1M sodium chloride, and 4M urea at 25 C 17 The moisture content of the chitosan as supplied was determined by heating at 60 C to constant weight in a vacuum oven and recording the weight loss. The calculated moisture content of 13.5% by weight reflected the hydrogel properties of chitosan.…”
Section: Methodsmentioning
confidence: 99%
“…Murphy et al 25 reported that the MIC of vancomycin for gram-positive endophthalmitis causing pathogens is 4 mg/L and in the majority of cases is in the range of 0.5 to 1.0 mg/L. 26,27 The sensitivity of the fluorescent polarization immunoassay (TDx-FLx System Abbott) was 2 lg/mL.…”
Section: Pharmacokinetics Of Topically Applied Vancomycin In Rabbit Eyesmentioning
confidence: 99%